2023
DOI: 10.16984/saufenbilder.1339199
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antigenotoxic Effect of Quercetin Against Antiepileptic Drug Genotoxicity by Comet Analysis

Fadime CANBOLAT,
Nihan AKINCI KENANOĞLU,
Tuğba Nurcan YÜKSEL
et al.

Abstract: Valproic acid (VPA) is among the most commonly used antiepileptic drugs in childhood and adult epilepsy. Although VPA is well tolerated, it can cause life-threatening side effects. VPA has toxic and genotoxic effects. Antioxidants can reverse drugs' toxic and genotoxic effects. Therefore, our study aimed to evaluate the antigenotoxic protective effect of quercetin (QUE) against VPA genotoxicity by in vitro comet assay analysis method. Comet assay analysis was performed in five different groups. Group I; negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Many studies highlight the potential protective effect of Que on drug toxicity. Canbolat et al (2023) reported in an in vitro comet assay study that Que has a protective effect against genotoxic damage that may occur with VPA [8].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies highlight the potential protective effect of Que on drug toxicity. Canbolat et al (2023) reported in an in vitro comet assay study that Que has a protective effect against genotoxic damage that may occur with VPA [8].…”
Section: Introductionmentioning
confidence: 99%